2011
DOI: 10.2139/ssrn.1797591
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Heterogeneity in Self-Assessed Health Among Elderly Europeans: The Impact of Mental and Physical Health Status

Abstract: Self-assessed health (SAH) is a frequently used measure of individuals" health status. It is also prone to reporting heterogeneity. To control for reporting heterogeneity valid measures of the objective health status are needed. The topic becomes even more complex for cross-country comparisons, as many key variables tend to vary strongly across countries, influenced by cultural and institutional differences. This study aims at exploring the key drivers for reporting heterogeneity in SAH in an international con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This is particularly important as the majority of the existing literature has focused either on mortality or self-reported health. The latter of which is subject to substantial problems of reporting bias, as we, and others (Barford et al 2010;Jurges 2007;Pfarr et al 2011) have noted.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This is particularly important as the majority of the existing literature has focused either on mortality or self-reported health. The latter of which is subject to substantial problems of reporting bias, as we, and others (Barford et al 2010;Jurges 2007;Pfarr et al 2011) have noted.…”
Section: Discussionmentioning
confidence: 59%
“…Using data from the first wave of SHARE, Jurges (2007) found that, independent of underlying health, there were significant differences between countries in the proportion of people who reported their overall health as 'good'. Similarly, Pfarr et al (2011) showed (also using SHARE data) significant differences in the proportion of people reporting their health as 'poor', independent of their 'true' health status. More importantly for the present study, Pfarr et al (2011) also showed differences between countries in the likelihood that people would report being physically limited by the same specific disease.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This issue may lead to discrepancies between the SRH and the true health of individuals; some individuals may be more inclined to rate themselves as having better (or worse) health than others even when their true health status is identical. Studies have shown that the threshold health levels may vary by sex (Lindeboom and van Doorslaer, 2004;Kapteyn et al, 2007), age (Groot, 2000;Van Doorslaer and Gerdtham, 2003;Lindeboom and van Doorslaer, 2004;Kapteyn et al, 2007), education (Hernandez-Quevedo et al, 2005;Kapteyn et al, 2007;Pfarr et al, 2011), income (Hernandez-Quevedo et al, 2005 and country of residence (Jürges, 2007;Kapteyn et al, 2007). It has also been argued that the threshold health levels may change over time due to: "changes in social and professional norms, access to health services, and individual behaviour that influence the recognition and classification of symptoms and demand for health care" (Sadana et al, 2000, p. 18).…”
Section: Introductionmentioning
confidence: 99%